2018
DOI: 10.1111/all.13388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pollen‐induced allergic rhinitis with high pollen exposure in grasslands of northern China

Abstract: BackgroundThe aim of this study was to investigate the prevalence of epidemiologic and physician‐diagnosed pollen‐induced AR (PiAR) in the grasslands of northern China and to study the impact of the intensity and time of pollen exposure on PiAR prevalence.MethodsA multistage, clustered and proportionately stratified random sampling with a field interviewer‐administered survey study was performed together with skin prick tests (SPT) and measurements of the daily pollen count.ResultsA total of 6043 subjects comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 39 publications
3
118
0
1
Order By: Relevance
“…Aeroallergens (pollens, molds, and HDM) are important inhaled particles and major causes of AR. Wang and colleagues reported that in Northern China, the prevalence of epidemiologic and pollen‐induced AR is 32.4% and 18.5%, respectively. Several studies showed that the incidence or severity of AR is closely correlated with levels of pollen allergens in ambient air in multiple countries and regions .…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aeroallergens (pollens, molds, and HDM) are important inhaled particles and major causes of AR. Wang and colleagues reported that in Northern China, the prevalence of epidemiologic and pollen‐induced AR is 32.4% and 18.5%, respectively. Several studies showed that the incidence or severity of AR is closely correlated with levels of pollen allergens in ambient air in multiple countries and regions .…”
Section: Mechanismsmentioning
confidence: 99%
“…33,36,41,42 Climate change affects vegetation, resulting in changes in the start, duration, intensity, and distribution of allergenic pollen. 33,36,41,43,44 Biedermann et al 36 have shown that climate change has increased the levels of birch pollen and period of exposure, with a higher prevalence of birch pollen sensitization. The extremely high prevalence of pollen-induced AR in the grasslands of Northern China is associated with high seasonal pollen exposure influenced by local environmental and climate conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the epidemic of AR in some major cities of China has increased considerably. A high prevalence of AR (18.6–52.9%) and physician-diagnosed AR (10.5–31.4%) has also been seen in northern China where gross pollen levels are high [4]. The prevalence of sensitization to aeroallergens in patients with AR also increased from 69.7 to 76.6% in Guangzhou in 2005–2014 [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter epidemiologic study in China revealed that grass pollens were the most prevalent sensitizing aeroallergens in north China; in particular, sensitization rates for Artemisia pollen were 58.2% in northwest China . Another epidemiological study in the northern grassland regions of China also suggested that grass pollens were the most common allergens . Our previous studies have indicated that major airborne pollen allergens are derived from grass during July to September in Beijing, China; the major pollens are Artemisia L., Chenopodium album , and Humulus scandens…”
mentioning
confidence: 97%